Association between endometrial cancer and subsequent risk of fracture: a national cohort study - Tsai, Wen-Hsuan; Hsu, Min-Shu; Weng, Chia-Sui; Hsu, Hsin-Yin; Hsieh, Cheng-Tzu; Yeh, Tzu-Lin; Chien, Kuo-Liong; Lee, Chun-Chuan; Chien, Ming-Nan; Tsai, Ming-Chieh (Frontiers in Endocrinology, 2025)
AimsMost endometrial cancer (EC) cases are estrogen-dependent, and some are associated with diabetes mellitus (DM). We aimed to estimate the risk of fracture among patients with EC and those with DM.Materials and methodsA total of 20814 patients with EC were identified from the Taiwan National Cancer Registry from 2007 to 2018, with the outcome ascertainment using the National Health Insurance Research Database from 2004 to 2019. This observational study investigated the hazard ratios (HRs) for fracture and mortality events using Cox proportional hazards regression, with 95% confidence intervals (CIs). We adjusted baseline comorbidities, cancer therapy, cancer staging and grade, and pathological status of estrogen receptor and progesterone receptor. Considering the competing death events, we estimated the subdistribution hazard model to predict the probability of the fracture risk in the competing risks context.ResultsAmong 15,505 EC patients, there were 3,044 patients with and 12,461 patients without DM. Patients with EC exhibited a no significant association of fracture when compared to the matched general population. EC patients with DM, compared to those without DM, had a significantly increased odds of osteoporotic fracture (HR 1.29 [95% CI 1.08–1.55]), hip fracture (HR 2.37 [95% CI 1.44–3.92]), and vertebral fracture (HR 1.71 [95% CI 1.06–2.74]). Patients with DM had a no significant association of upper extremity fracture (HR 1.33 [95% CI 0.95–1.87]) compared with those with EC but without DM.ConclusionsEC patients had a no significant association of fracture, while DM increased the fracture risk in EC patients.